Application of The Make A Match Model to Improve The Learning Outcomes of Class II Students in Elementary Schools - Laili Mutia Qodra; Cecil Hiltrimartin; Destiana Wati (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to improve the learning outcomes of class II students through the Make a Match learning model at State Elementary School 07 Palembang. This type of research is classroom action research carried out over two cycles. The subjects of this research were 30 students. Methodology: The techniques used for data collection are tests, observation, and documentation. The data analysis technique used is qualitative and quantitative data analysis. The research results show that learning outcomes using the Make a Match type cooperative learning model have increased in Indonesian language subjects. Main Findings: This can be seen from before the action. The average student score was only 61.83, with a completion percentage of only 60%. In cycle I, the average student score was 68, 47, with a completion percentage reaching 73%. In cycle II, the average student score was 76.30, and the completion rate reached 83%. Novelty/Originality of this study: The latest research applies the make-a-match learning model to Indonesian language subjects. Thus, using the make-a-match type cooperative learning model can improve the learning outcomes of class 2 students in Indonesian language subjects.